2022
DOI: 10.3389/fendo.2022.1080285
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and pathological roles of Ang II and Ang- (1-7) in the female reproductive system

Abstract: The local Renin-Angiotensin System (RAS) has been demonstrated to exist in a wide range of tissues and organs, In the female reproductive system, it is mainly found in the ovary, uterus and placenta. The RAS system is made up of a series of active substances and enzymes, in addition to the circulating endocrine renin-angiotensin system. The active peptides Angiotensin II (Ang II) and Angiotensin (1-7) (Ang-(1-7)), in particular, appear to have distinct activities in the local RAS system, which also controls bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 133 publications
0
3
0
1
Order By: Relevance
“…For in vitro research on endometrial receptivity and embryo implantation, the commonly utilized human-sensitive endometrial Ishikawa and RL95-2 cells both express ACE1, ACE2, and TMPRSS2 transcripts and proteins. Since the ACEIs used in the current study did not affect the expression of ACE1, ACE2, and TMPRSS2 or the attachment of the spheroid to the Ishikawa cells, this suggests that using ACEIs to treat diseases may not have an impact on endometriosis and subsequent embryo implantation ( 35 ).…”
Section: Angiotensin-converting Enzyme 1 In Endometrial Cancermentioning
confidence: 81%
“…For in vitro research on endometrial receptivity and embryo implantation, the commonly utilized human-sensitive endometrial Ishikawa and RL95-2 cells both express ACE1, ACE2, and TMPRSS2 transcripts and proteins. Since the ACEIs used in the current study did not affect the expression of ACE1, ACE2, and TMPRSS2 or the attachment of the spheroid to the Ishikawa cells, this suggests that using ACEIs to treat diseases may not have an impact on endometriosis and subsequent embryo implantation ( 35 ).…”
Section: Angiotensin-converting Enzyme 1 In Endometrial Cancermentioning
confidence: 81%
“…Moreover, this study demonstrated the antitesticular aging effect of NTs at the animal level, which can be further verified by conducting population experiments. Furthermore, this experiment only explored the effects of NTs on testosterone levels in male mice; however, it has been shown that the local RAS also regulates female reproductive functions [61,62], and the effects on female ovaries could be explored next, which could help to explore the effects of exogenous NTs on the reproductive system more comprehensively.…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews have recently discussed Ang II and the promotion of cancer ( 9 , 20 , 21 , 22 , 23 , 24 , 25 ). The Ang II/AT1 axis promotes activation of a number of proteins and pathways associated with cell proliferation including epidermal growth factor receptor activation, Janus kinase-signal transducers and activators of transcription signaling, and mitogen-activated protein kinase activation ( 26 , 27 , 28 ).…”
Section: How Ang II Affects Cancermentioning
confidence: 99%